Effect of non‐alcoholic beer containing matured hop bitter acids on mood states in healthy adults: A single‐arm pilot study. (9th December 2021) - Fukuda, Takafumi; Akiyama, Shiori; Takahashi, Kazuyuki; Iwadate, Yasuo; Ano, Yasuhisa
Abstract: This study aimed to investigate the effect of non‐alcoholic beer containing matured hop bitter acids on mood states among healthy adults older than 20 years. This study was an open‐label longitudinal intervention design in which each participant served as their control. For 3 weeks, we evaluated the effect of non‐alcoholic beer containing 35 mg of matured hop bitter acids on mood, sleep quality, and work performance. The data of 97 participants (age range: 23–72 years, median age: 42) were analyzed. After the intervention, we found that matured hop bitter acids significantly improved total mood state, including anxiety, depression, fatigue, and vigor, compared with the baseline. Furthermore, sleep quality and absolute presenteeism were significantly improved after the intervention compared with the baseline. The present exploratory study suggested that 3‐week supplementation with matured hop bitter acids improved mood and peripheral symptoms in persons of a wide range of ages. Although further investigation is needed, the findings suggested that non‐alcoholic beer in daily life might become a choice for maintaining mood states.